Dye exclusion technique to assess the viability of pre-implantation bovine embryo based on a murine model - SINGH, GURVINDERJIT; PANGAONKAR, G R; MATHAROO, JOGA SINGH; SINGH, PRAHLAD; SINGH, MEHAR (The Indian Journal of Animal Reproduction, 2023)
Dye exclusion assay was evaluated for assessing viability of pre-implantation murine and bovine embryosalong with morphological examination of sucrose-induc
Keywords: Viability assay; dye; murine embryo; bovine embryo